Pengaruh Pemberitaan Efek Samping Vaksin Terhadap Minat Masyarakat Untuk Melakukan Vaksinasi - Safrilla Saronto; Weni A. Arindawati; Oky Oxcygentri (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The advantages and drawbacks of how the general public views the anticipated adverse effects of the COVID-19 vaccine, which some are concerned about when immunized, are the driving forces behind this research. The purpose of this study is to ascertain how news of vaccine adverse effects affects vaccination interest. The sample of this study was 88 respondents as research participants. The technique used is descriptive quantitative, which combines direct linear regression analysis, using the theory of Uses and Effects. Karangligar Village residents who have never been vaccinated participated in this study. Simple linear regression was employed in this study to evaluate the data. According to the study's findings, there is a substantial relationship between the news's fervor and Karangligar Village residents' enthusiasm in receiving the COVID-19 vaccination. And the interest in immunizing the residents of Karangligar Village is significantly influenced by the media's coverage of the COVID-19 vaccine's negative effects. Keywords: News; COVID-19; Vaccination